Pengaruh Kemudahan Penggunaan, Kualitas Pelayanan dan Persepsi Keamanan Terhadap Keputusan Penggunaan Mobile Banking bagi Mahasiswa Fakultas Ekonomi UKI Toraja - Andarias Buttu Kayang; Helba Rundupadang; Jens Batara Marewa (CV. Ulil Albab Corp, 2024)
The research objectives Namely to determine the simultaneous influence of ease of use, Service quality and security perceptions on mobile usage decisions banking for UKI Toraja economics faculty students. Type of research used in this research is quantitative research. The research results are (1) ease of use influences the decision to use. (2) Service quality influences usage decisions. (3) perception security influences usage decisions